Medical Liability of Residents in Taiwan Criminal Court: An Analysis of Closed Malpractice Cases - Kuan-Han Wu; Po-Chun Chuang; Chih-Min Su; Fu-Jen Cheng; Chien-Hung Wu; Fu-Cheng Chen; Yii-Ting Huang (Emergency Medicine International)
Objective. By analyzing closed criminal malpractice claims involving resident physicians, we aimed to clarify the characteristics of litigations and examine the litigious errors leading to guilty verdicts. Design. A retrospective descriptive study. Setting/Study Participants. The verdicts pertaining to physicians recorded on the national database of the Taiwan justice system were reviewed. Main Outcome Measures. The characteristics of litigations were documented. Negligence and guilty verdicts were further analyzed to identify litigious errors. Results. Between January 1, 2000, and December 31, 2014, from a total of 436 closed criminal malpractice cases, 40 included resident physicians. Five (12.5%) cases received guilty verdicts with mean imprisonment sentences of 5.4 ± 4.1 months. An average of 77.2 months was required for the final adjudication, and surgery residents were involved most frequently (38.9%). Attending physicians were codefendants in 82.5% of cases and were declared guilty in 60% of them. Sepsis (37.5%) was the most common disease in the 40 cases examined, followed by operation/procedure complications (25%). Performance errors (70%) were more than twice as common than diagnostic errors (30%), but the percentage of guilty verdicts in performance error cases was much lower (7.1% vs. 25%). Four negligence cases received nonguilty verdicts, which were mostly due to lack of causation. Conclusion. Closed criminal malpractice cases involving residents took on average 6.22 years to conclude. Performance errors accounted for 70% of cases, with treatment of sepsis and operation/procedure complications predominant. To reduce medicolegal risk, residents should learn experiences from analyzing malpractice cases to avoid similar litigious pitfalls.